Level of Difficulty in Developing Android-Based Learning Media - Setiyani, Susanti; Liantoni, Febri; Hatta, Puspanda (Universitas Pendidikan Ganesha, 2023)
One of the teacher's competencies is designing and producing learning media; there are various types of learning media, one of which is Android-based. A complex relationship between technology and theory drives the development domain, including design, production, and delivery functions. This research aims to analyze the difficulty level in developing Android-based learning media. The subjects of this research were 30 PTIK students who had developed Android learning media and user testing. Data collection was carried out using research instruments in the form of questionnaires. The data obtained was analyzed using descriptive statistics and then categorized into three development difficulty levels: high, medium, and low. The results of the analysis show that the student's level of difficulty is in the medium category with a percentage of 77%, where the highest level of difficulty is in the developing aspect with a high category percentage of difficulty of 13%, in the design aspect it is 10%, the analysis aspect is 7%, the implementation aspect is 7%, Meanwhile, in the evaluation aspect, there were no students with difficulties in the high category. The research concludes that development difficulties lie in activities in development software, such as the asset upload process, and are then related to understanding the programming structure and the ability to provide development needs, such as test equipment and suitability of device specifications.